Open label feasibility study evaluating D‐mannose combined with home‐based monitoring of suspected urinary tract infections in patients with multiple sclerosis. Issue 7 (4th November 2016) - Phé, Véronique; Pakzad, Mahreen; Haslam, Collette; Gonzales, Gwen; Curtis, Carmel; Porter, Bernadette; Chataway, Jeremy; Panicker, Jalesh N.
Abstract : Objective: To assess the feasibility of using D‐mannose, a natural food supplement, in patients with multiple sclerosis (MS) reporting recurrent urinary tract infections (UTIs) as a preventative. Methods: A single‐center, open‐label, feasibility study enrolled patients with MS, using and not using urinary catheters, experiencing recurrent UTIs (≥3/year or ≥2/6 months). Participants were given D‐mannose powder 1.5 grams twice daily for 16‐weeks and were instructed to monitor suspected UTIs at home using urine dipsticks. Diaries were used to record compliance, number of prescriptions of antibiotics received for UTIs, results of urine dipsticks and cultures. Results: Overall, 22 patients with MS, median age 50 years (46–59) were enrolled: 10 were not using catheters and 12 were using catheters. The compliance rates for using D‐mannose and dipsticks for testing suspected UTIs were 100% and 90.2%, respectively. Sixty‐one episodes of suspected UTIs were recorded, 19/61 (31.1%) were confirmed UTIs and 29/61 (47.5%) prescriptions of antibiotics were made. The number of monthly proven UTIs decreased both in catheter users and non‐users ( P  < 0.01). No adverse effects were reported. Conclusion: Using D‐mannose in patients with MS experiencing recurrent UTIs and self‐monitoring for infections is feasible and safe. Further studies are required to establish efficacy.CinicalTrials.gov (identifier NCT02490046) .